Legal regulation of temporary protection of displaced persons from Ukraine in the EU countries - Kalynovskyi, Bohdan (Migration & Law, 2023)
The article is devoted to the study of theoretical and practical issues of legal regulation of temporary protection of displaced persons from Ukraine in the European Union. The author analyses the Council Directive 2001/55/EC on minimum standards for the provision of temporary protection in cases of mass influxes of displaced persons and on measures to maintain a balance in the efforts of Member States in connection with the reception and consequences of such reception of 20 July 2001 and national legal acts of EU countries regulating the conditions and procedure for obtaining temporary protection. The author examines the concepts of “temporary protection”, “displaced persons” and “mass influx”. The author emphasises that “temporary protection” should be understood as an exceptional procedure aimed at providing immediate and temporary protection to displaced persons in the event of a mass influx or an anticipated mass influx from third countries who are unable to return to their country of origin, in particular, when there is a risk that the asylum systems of Member States will not be able to cope with a large influx without reducing the efficiency of their functioning for the persons concerned and other persons seeking protection. The article highlights the issues and peculiarities of granting temporary protection in the EU countries. On the example of the legislation of the Republic of Poland and the Czech Republic, the author analyses the categories of persons entitled to apply for temporary protection in these countries.